Effect of energy metabolism and proteolysis on the toughness of intermediate ultimate pH beef. (June 2022) - Zhao, Yan; Kong, Xiao; Yang, Xiaoyin; Zhu, Lixian; Liang, Rongrong; Luo, Xin; Zhang, Liang; Hopkins, David L.; Mao, Yanwei; Zhang, Yimin
Abstract: The objective of this study was to identify the tenderness and energy metabolism attributes in normal ultimate pH (pHu, 5.4–5.8, NpHu ), intermediate pHu (5.8–6.2, IpHu ) and high pHu (> 6.2, HpHu ) Longissimus lumborum from beef. During 21 days of aging, the IpHu group exhibited a higher Warner-Bratzler shear force, lower activity of μ-calpain, and a higher content of heat shock protein 27 and greater protein oxidation. Metabolomics analysis revealed that 24 differential metabolites were detected during the first 24 h postmortem between pH groups, and these were mainly the products of glycolysis, the tricarboxylic acid (TCA) cycle and oxidative phosphorylation. The relatively higher adenosine triphosphate content in the IpHu group could delay tenderization by being used as key substrate for protein phosphorylation. In addition, the relationship between guanosine triphosphate, diphosphate and monophosphate, and beef tenderness was worthy to be verified in the future study.